Ecclesiastical landscapes in medieval Europe : an archaeological perspective - Sánchez-Pardo, José Carlos; Marron, Emmet; Țiplic, Maria Emilia (Archaeopress, 2020)
By presenting case studies from across Eastern and Western Medieval Europe, this volume aims to open up a Europe-wide debate on the variety of relations and contexts between ecclesiastical buildings and their surrounding landscapes between the 5th and 15th centuries AD.